Oviposition behavior and fecundity of Clostera cupreata (Butler) (Lepidoptera: Notodontidae) on different poplar clones - Singh, Ravinder; Kaur, Gurlaz; Sangha, K.S. (Indian Journal of Agroforestry, 2020)
Poplar, Populus deltoides Bartr Ex Marsh, is cultivated for plywood and timber and its production is hampered by a number of insect pests. The insect pests complex of poplar comprise of a number of defoliator species along with other insects and Clostera cupreata (Butler) is one of the important defoliator infesting poplars in North-Western India. Host plant resistance is an important aspect of integrated pest management and thus screening of different poplar clones for resistance to insect pests is necessary. Keeping this objective in view, evaluation studies on PL7, L47/88 and G48 clones for oviposition and fecundity of C. cupreata were performed at Forestry Research Area, Punjab Agricultural University, Ludhiana and Forest Protection laboratory, Department of Forestry and Natural Resources, PAU, Ludhiana, India. Results indicated that clones did not influence oviposition behaviour. However, lower leaf surface was preferred for egg laying in all the clones. Oviposition preference on different plant parts was in the order: lower leaf surface > upper leaf surface > twig. Fecundity was the maximum during October and minimum during June. Overall means represented that fecundity was comparatively lower on PL7 as compared to L47/88 and G48 clones.